2023
DOI: 10.1037/ser0000619
|View full text |Cite
|
Sign up to set email alerts
|

Cultural adaptations of motivational interviewing: A systematic review.

Abstract: Motivational interviewing (MI;Miller & Rollnick, 2012) has expanded from treating substance use disorders to other health concerns across a range of racial-ethnic groups and ages. The spirit of MI lends itself well to working with culturally diverse populations by eliciting the client's values and goals in a collaborative and client-centered approach in pursuit of behavior change. Additionally, MI has been further adapted for use with racial-ethnic minority groups to enhance its effectiveness with specific pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…intervention is culturally tailored (Dickerson et al, 2018;Lee et al, 2013;Self et al, 2022;Venner et al, 2008), or efforts are made to integrate the client's cultural context (Bahafzallah et al, 2020).…”
Section: Cross-cultural Rigor Of Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…intervention is culturally tailored (Dickerson et al, 2018;Lee et al, 2013;Self et al, 2022;Venner et al, 2008), or efforts are made to integrate the client's cultural context (Bahafzallah et al, 2020).…”
Section: Cross-cultural Rigor Of Assessmentsmentioning
confidence: 99%
“…There is strong research support for utilizing an MI-spirit during the unstructured interview to enhance retention (Lappan et al, 2020). Additionally, MI has demonstrated effectiveness for use with racial/ethnic minoritized groups, particularly when the intervention is culturally tailored (Dickerson et al, 2018; Lee et al, 2013; Self et al, 2022; Venner et al, 2008), or efforts are made to integrate the client’s cultural context (Bahafzallah et al, 2020).…”
Section: Summary Of Review Findingsmentioning
confidence: 99%
“…Such reviews move the field forward by identifying how mental health services can be provided in a culturally responsive manner to meet the needs of diverse populations. Self et al (2023) conducted a systematic review of articles assessing cultural adaptations of motivational interviewing (CAMI). Twenty-five peer review studies consisting of eight pilot studies and 17 randomized control trials (RCTs) were included.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Self et al (2023) conducted a systematic review of articles assessing cultural adaptations of motivational interviewing (CAMI). Twenty-five peer review studies consisting of eight pilot studies and 17 randomized control trials (RCTs) were included.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…The key feature of the MI approach is a goal-oriented and client-centred conversation style, distinct from non-directive Rogerian humanistic psychotherapy [ 1 ]. A systematic review analysed 25 peer-reviewed MI studies and showed that those cultural adaptations of MI propounded significant improvement in treatment outcomes compared to the control condition [ 3 ]. However, the efficacy was demonstrated in varying populations and diverse settings, with over 3000 randomised controlled trials [ 4 ], for example, cannabis use [ 5 ], cancer screening [ 6 ], probation [ 7 ], attention-deficit/hyperactivity disorder [ 8 ], school prevention [ 9 ] and COVID-19 vaccination hesitancy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%